Review of SHELL gene-based marker used in determining fruit form of Elaeis guineensis - Zulkifli, Amirul Akmal; Mohd Asri, Nurul Ain Shahira; Midin, Mohd Razik; Wan Hanafi, Wan Nurhayati (e-International Publishing House Ltd., 2023)
Elaeis guineensis, commonly known as the African oil palm, holds a prominent position as the world's leading commercialized oil palm species. The shell thickness of the fruit plays important role in oil production. E. guineensis exhibits three fruit form: dura (female), tenera (male), and pisifera, which is a hybrid resulting from the crossbreeding of dura and pisifera palms. The differentiation of these fruit forms relies on the shell thickness of the fruit, controlled by the SHELL gene. The objective of this revies is to comprehensively analyze and summarize the existing literature on the application and effectiveness of SHELL gene -based markers in determining fruit form variation in Elaeis guineensis (oil palm).